Sheep and guanaco effects on plant regeneration of two Patagonian shrub steppes - Pecile, Maria Valeria (2026)
In the Patagonian drylands, extensive sheep production coexists with guanaco, the most abundant native herbivore.While sheep’s impacts on vegetation are well known, guanaco effects remain poorly understood, limiting effective management. We evaluated the influence of both species on grassland regeneration at two representative sites by comparing areas grazed by sheep or guanaco and applying short-term herbivore exclusions. We analyzed pre-and post-dispersal soil seed banks in vegetated patches and bare soil, and measured seedling emergence and tiller production of dominant perennial grasses. The soil seed bank was dominated by annual species, and vegetated patches showed higher perennial abundance after seed dispersal, but no significant differences emerged between herbivores. Seedling emergence was similar for sheep and guanaco, increasing notably after short-term exclusion. However, perennial grass regeneration through tillering responded differently :guanaco exclusion enhanced tillering of Nassella tenuis an Pappo stipa speciosa, whereas sheep exclusion produced no significant effect. Overall, most regeneration mechanisms showed comparable patterns under both herbivores. These findings suggest that, although guanaco and sheep exert similar pressures on seedling dynamics, guanaco grazing may differently affect perennial grass recovery. We emphasize the need for careful monitoring of guanaco stocking rates to ensure sustainable management of Patagonian shrub-steppe ecosystems.